Ubud: Benteng Terbuka - Graeme MacRae (Jurnal Kajian Bali (Journal of Bali Studies), 2014)
This article discusses evolution and present problems of Ubud as a tourist town in the context of Bali tourism development. Ubud has always provided an alternative vision of what tourism in Bali could be. The metaphor of an Open Fortress provides a useful lens for looking at Ubud over the past century. “Tourism” is in Ubud has always been closely linked to an expatriate community and other international economic activities. Tourism is not a oneway process – it is always a dialectical process between local communities and visitors (as Michel Picard told us long ago). This process is always changing and in Ubud it has now entered a new phase – involving a tourism/expat nexus that is quite disconnected from local community and culture.